Jejak Sejarah Tradisi Intelektual Nahdlatul Ulama pada Masa Awal Pendirian (1920-an) - Devitasari, Amelia Chintya; Aulivia Putri, Frisca Diana; Birsyada, Muhammad Iqbal (Estoria: Journal of Social Science and Humanities, 2025)
This study examines the historical traces and intellectual traditions of Nahdlatul Ulama (NU) in its early days, focusing on NU's role in the struggle for Indonesian independence and the development of moderate and progressive religious and socio-political traditions. The background of this study is based on the importance of understanding how NU, as a religious organization rooted in the Ahlus Sunnah wal Jamaah tradition and Islamic boarding schools, contributed to maintaining local Islamic identity, fighting Dutch colonialism, and strengthening the unity and nationalism of Muslims in Indonesia. The method used is a literature review with content analysis techniques. It collects and examines various secondary sources in the form of scientific articles, books, and research related to NU's intellectual tradition and its socio-political role. The study results show that NU has succeeded in integrating traditional values with contextual renewal of thought, through the teaching of yellow books in Islamic boarding schools and the Jihad Resolution fatwa that motivates the struggle for independence. NU also plays an active role in building a network of ulama, strengthening traditional Islamic education, and developing a nationalist movement that rejects identity politics and prioritizes moderate and tolerant Islam. The implications of this research confirm that NU is not only a normative religious organization but also a progressive and adaptive socio-political force in facing the challenges of modernity and colonialism, and has a strategic role in shaping the character of the nation and maintaining national harmony in Indonesia.